Comparison of Indonesian students’ experiences in Japan and Indonesia: understanding global governance and self-efficacy in work readiness - Diyah Rachmawati Tohari (Journal of Contemporary East Asia Studies)
Globalization has intensified global interconnectedness and interdependence, demanding that higher education graduates possess global skills and knowledge. Internationalization of higher education aims to address these challenges. Students must understand global governance and develop a sense of global responsibility to participate effectively in international decision-making. Bandura’s Social Learning Theory (SLT) and Social Cognitive Theory (SCT) offer valuable insights into how students navigate internationalization. These theories suggest that students learn through observation and interaction with their environment, shaping their understanding of global citizenship and job readiness. This study compares the experiences of Indonesian students studying in International Programs at Universities in Japan and Indonesia, focusing on their understanding of global governance and self-efficacy in job readiness. Through qualitative interviews with 21 students, the research finds significant differences between the two countries’ approaches to internationalization. Students in Japan benefit from extensive global exposure through international internships and case studies, yet face challenges integrating with local Japanese communities, which affects their self-efficacy for adapting to local work environments. Conversely, Indonesian students gain valuable local engagement through the Kuliah Kerja Nyata (KKN) program, enhancing their ability to address local challenges despite limited global exposure. The discussion suggests that combining global solid exposure and local interaction can better prepare students for global and domestic job markets, making them more adaptable and competitive. These findings highlight the importance of balancing global and local experiences in internationalization strategies.